2020
DOI: 10.1002/ana.25814
|View full text |Cite
|
Sign up to set email alerts
|

Report on Electroencephalographic Findings in Critically Ill Patients with COVID‐19

Abstract: In March 2020, we treated a cohort of 26 critically ill hospitalized SARS‐CoV‐2–infected patients who underwent electroencephalography to assess unexplained altered mental status, loss of consciousness, or poor arousal and responsiveness. Of the 26 patients studied, 5 patients had electroencephalograms that showed periodic discharges consisting of high‐amplitude frontal monomorphic delta waves with absence of epileptic activity. These findings may suggest central nervous system injury potentially related to CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 20 publications
2
44
1
2
Order By: Relevance
“…While there has been concern that intranasal infection may be a potential route for coronavirus neuroinvasion 24 , there was no clear association between epileptiform findings and anosmia, nor was there a fronto-temporal predominance to suggest specifically limbic involvement. Other groups have noted frontally predominant abnormalities in patients with SARS-CoV-2 7,8,25,26 , but in at least one paper frontal slowing appeared similar to that seen in metabolic encephalopathies and correlated with systemic lab findings 7 . Although a few encephalitides are associated with suggestive EEG findings, such as very low frequency periodic complexes in measles-related subacute sclerosing panencephalitisis 27 or lateralized periodic epileptiform discharges in HSV encephalitis 28 , neither finding is necessarily specific.…”
Section: Sars-cov-2 and Epileptiform Eeg Findingsmentioning
confidence: 71%
See 1 more Smart Citation
“…While there has been concern that intranasal infection may be a potential route for coronavirus neuroinvasion 24 , there was no clear association between epileptiform findings and anosmia, nor was there a fronto-temporal predominance to suggest specifically limbic involvement. Other groups have noted frontally predominant abnormalities in patients with SARS-CoV-2 7,8,25,26 , but in at least one paper frontal slowing appeared similar to that seen in metabolic encephalopathies and correlated with systemic lab findings 7 . Although a few encephalitides are associated with suggestive EEG findings, such as very low frequency periodic complexes in measles-related subacute sclerosing panencephalitisis 27 or lateralized periodic epileptiform discharges in HSV encephalitis 28 , neither finding is necessarily specific.…”
Section: Sars-cov-2 and Epileptiform Eeg Findingsmentioning
confidence: 71%
“…One early series of patients with severe infection described neurologic findings of impaired consciousness (14.8%) and seizure (1.1%) 3 , while another noted that 27% of patients had seizure risk factors, though clinical seizures appeared rare 4 . However, routine EEG data to support or contextualize these concerns has been limited to smaller series [5][6][7][8] , with some series abstaining from EEGs altogether due to safety concerns 4 , including limited personal protective equipment (PPE), risks of technician exposure, and possible iatrogenic spread through personnel or equipment contamination. A paucity of EEGs could underestimate the rate of seizures and epileptiform activity in SARS-CoV-2, given reports of seizures in other coronavirus outbreaks 9 and reports of patients with SARS-CoV-2 with nonconvulsive or focal status epilepticus 10,11 .…”
Section: Introductionmentioning
confidence: 99%
“…14,[27][28][29] A recent study reviewing EEG findings from a cohort of 26 critically ill patients who underwent EEG testing in France did not report any seizures, but highlighted findings consistent with encephalopathy in these patients. 30 As with infectious processes in general, patients with pre-existing epilepsy may experience seizure exacerbations in the setting of COVID-19. Of interest we found that 15% of patients without a history of epilepsy experienced clinical or EEG seizures, although it is likely that not all "clinically probable" seizures prior to EEG testing were true seizures, as there are mimics of seizures in the critically ill population (eg, myoclonus, movement disorders, or cardiac events).…”
Section: Discussionmentioning
confidence: 99%
“…Relatively small cohorts of patients with COVID-19 and EEG are published to date, with the patients in these studies only undergoing routine duration or reduced montage EEG recording, for the reasons discussed above, and less frequently continuous EEG monitoring. Several authors observed sporadic epileptiform abnormalities and periodic patterns of concern, including generalized periodic discharges, along with more expected patterns of generalized slowing ( 22 26 ). Due to centers taking precautions to avoid transmission risk by reducing staffing and utilization of EEG, as well as obtaining imaging, cases of electrographic seizures and NCSE may be less likely to be diagnosed and adequately imaged.…”
Section: Discussionmentioning
confidence: 99%